Business process runtime models: towards bridging the gap between design, enactment, and evaluation of business processes - Goldstein, A.; Johanndeiter, T.; Frank, U. (Information Systems and e-Business Management. Vol. 17, 2019)
Business process management (BPM) broadly covers a lifecycle of four distinct phases: design, configuration, enactment, and analysis and evaluation. Most BPM tool suites impose a strict separation between these phases, i.e., in each phase different languages and tools are used and the transition between phases is indirect and costly. This paper presents an environment for integrating all phases of the BPM lifecycle in which business process (BP) types and their instances can be modeled, visualized, managed and automatically synchronized, using a shared representation of models and code. The environment extends the capabilities of BP models to be used not only for specifying BPs but also for: (1) enactment—creating instance objects that capture BP operational data; (2) monitoring BP instances as they progress; (3) visualizing performance indicators of executed BPs at runtime; and (4) navigating from a BP type model to its respective instance population. As opposed to existing tools, the proposed environment does not require regenerating the workflow schema when BP designs change, nor does it require additional adaptations to support monitoring. Thereby, we facilitate a continuous and dynamic BPM environment, where workflow specifications can be changed at runtime. Our solution integrates a meta-programming language called eXecutable Modeling Facility (XMF) and the multi-perspective enterprise modeling framework (MEMO).